2016
DOI: 10.1017/s1368980016002937
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dietary patterns and diet quality during pregnancy: a systematic review with narrative synthesis

Abstract: The framework was supported by the literature identified, but more research of sound methodology is needed in order to conclusively disentangle the interplay of the different determinants. Practitioners should be aware that pregnant women who are young, have a low education or do not follow general health advice appear to be at higher risk of inadequate dietary intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 50 publications
(222 reference statements)
10
90
3
3
Order By: Relevance
“…Additional nonmodifiable factors associated with dietary diversity included caste, education, and economic status. Our results are consistent with previous literature wherein maternal knowledge and socio‐economic status were found to be associated with dietary diversity (de Castro et al, ; Doyle, Borrmann, Grosser, Razum, & Spallek, ; Rosen et al, ; Shamim et al, ). Women belonging to higher caste and income groups were more likely to have a diverse diet, suggesting a resource constraint in adoption of diet recommendations beyond improved knowledge and counselling services.…”
Section: Discussionsupporting
confidence: 93%
“…Additional nonmodifiable factors associated with dietary diversity included caste, education, and economic status. Our results are consistent with previous literature wherein maternal knowledge and socio‐economic status were found to be associated with dietary diversity (de Castro et al, ; Doyle, Borrmann, Grosser, Razum, & Spallek, ; Rosen et al, ; Shamim et al, ). Women belonging to higher caste and income groups were more likely to have a diverse diet, suggesting a resource constraint in adoption of diet recommendations beyond improved knowledge and counselling services.…”
Section: Discussionsupporting
confidence: 93%
“…In the multivariate analysis, parity and household wealth index were both associated with a higher WDDS at preconception and with a positive change in the WDDS throughout follow‐up. The socioeconomic level of the household is a well‐known determinant of women's dietary diversity in African contexts (Doyle, Borrmann, Grosser, Razum, & Spallek, ; Huybregts et al, ; Krige et al, ; Rosen et al, ). Here, we showed that women with less economic constraints had better access to varied foods and were able to increase their dietary diversity during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…So far, two systematic reviews and a paper describing the study aims have been published. [9][10][11] Methodological papers on the recruitment of migrants for birth cohort studies in Germany and on data linkage of primary and secondary data using advanced statistical procedures were submitted or are in progress. Preliminary data analyses have been conducted regarding the determinants of antenatal stress and dietary patterns in pregnancy.…”
Section: Discussionmentioning
confidence: 99%